Analysis of the Cytoplasmic Domains of Salmonella FlhA and Interactions with Components of the Flagellar Export Machinery - McMurry, Jonathan L. (American Society for Microbiology, 2004)
Most flagellar proteins are exported via a type III export apparatus which, in part, consists of the membrane proteins FlhA, FlhB, FliO, FliP, FliQ, and FliR and is housed within the membrane-supramembrane ring formed by FliF subunits. Salmonella FlhA is a 692-residue integral membrane protein with eight predicted transmembrane spans. Its function is not understood, but it is necessary for flagellar export. We have created mutants in which potentially important sequences were deleted. FlhA lacking the amino-terminal sequence prior to the first transmembrane span failed to complement and was dominant negative, suggesting that the sequence is required for function. Similar effects were seen in a variant lacking a highly conserved domain (FHIPEP) within a putative cytoplasmic loop. Scanning deletion analysis of the cytoplasmic domain (FlhAc) demonstrated that substantially all of FlhAc is required for efficient function. Affinity blotting showed that FlhA interacts with several other export apparatus membrane proteins. The implications of these findings are discussed, and a model of FlhA within the export apparatus is presented.